1999
DOI: 10.1046/j.1464-5491.1999.00189.x
|View full text |Cite
|
Sign up to set email alerts
|

Metformin inhibits catecholamine‐stimulated lipolysis in obese, hyperinsulinemic, hypertensive subjects in subcutaneous adipose tissue: an in situ microdialysis study

Abstract: The present data demonstrate the effects of metformin on lipolysis in subcutaneous adipose tissue in vivo. In the large body fat mass of obese subjects, a reduction of lipolysis in adipose tissue may contribute to a decrease of VLDL synthesis in the liver resulting in a lowered plasma triglyceride concentration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 37 publications
1
26
1
Order By: Relevance
“…An in situ microdialysis study indicated that pre-perfusion of metformin inhibited the release of glycerol in vivo in abdominal adipose tissue of obese and hyperinsulinemic subjects after administration of catecholamine (Flechtner-Mors et al 1999). However, this study did not investigate the cellular basis by which metformin lowered glycerol release from adrenaline-stimulated adipose tissue.…”
Section: Discussionmentioning
confidence: 86%
“…An in situ microdialysis study indicated that pre-perfusion of metformin inhibited the release of glycerol in vivo in abdominal adipose tissue of obese and hyperinsulinemic subjects after administration of catecholamine (Flechtner-Mors et al 1999). However, this study did not investigate the cellular basis by which metformin lowered glycerol release from adrenaline-stimulated adipose tissue.…”
Section: Discussionmentioning
confidence: 86%
“…In addition, the patients received different forms of oral glucose-lowering pharmacotherapy, including metformin. Metformin can inhibit human lipolysis both in vivo and in in vitro adipocyte cultures [47,48]. However, the anti-lipolytic effect of metformin is observed only upon stimulated lipolysis, and should not affect the presently investigated spontaneous rate.…”
Section: Discussionmentioning
confidence: 99%
“…These blots are representative of two independent experiments results showing an anti-lipolytic effect of both metformin and the related biguanide phenformin in rodent adipocytes [8,40], attributed for the latter drug to an activation of AMPK. Moreover, in humans, a perfusion of metformin in microdialysis experiments has an anti-lipolytic effect [22,41].…”
Section: Discussionmentioning
confidence: 99%
“…The biguanide metformin decreases the high hepatic glucose output observed in type 2 diabetes, whereas thiazolidinediones such as pioglitazone or rosiglitazone increase muscle glucose uptake in response to insulin and are called insulin sensitisers. Metformin and thiazolidinediones have been reported to decrease the plasma concentrations of non-esterified fatty acids in type 2 diabetic patients [17][18][19][20][21] and the lipolytic rate in obese humans [22][23][24]. In rodent adipocytes, biguanides and thiazolidinediones are able to activate AMPK, and biguanides are able to reduce lipolysis [8,25,26].…”
Section: Introductionmentioning
confidence: 99%